2020
DOI: 10.1002/oby.23017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Telomere Length in Adipose Tissue and Leukocytes and its Association with Postsurgical Weight Loss

Abstract: ObjectiveThe aim of this study was to determine the relationship between telomere length (TL) in subcutaneous adipose tissue (SAT), visceral adipose tissues (VAT), and leukocytes, as well as to examine the associations of TL in these tissues with postsurgical weight loss in Asians with severe obesity.MethodsPresurgery TL was measured in leukocytes, SAT, and VAT of 91 patients who underwent weight loss surgery. Correlation between TL in multiple tissues was assessed using Pearson correlation. The association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The main limitation is that we studied mean LTL length, which does not necessarily translate to TL in tissues and cells relevant to the development of the MetS, for example adipose stem cells. However, TL within individuals is generally strongly correlated across tissues (Daniali et al, 2013 ; Demanelis et al, 2020 ; Gurung et al, 2020 ). Secondly, our findings are based on data from GWAS conducted in subjects of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation is that we studied mean LTL length, which does not necessarily translate to TL in tissues and cells relevant to the development of the MetS, for example adipose stem cells. However, TL within individuals is generally strongly correlated across tissues (Daniali et al, 2013 ; Demanelis et al, 2020 ; Gurung et al, 2020 ). Secondly, our findings are based on data from GWAS conducted in subjects of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…TL is generally measured in leucocytes due to the easy accessibility of these cells in peripheral blood. Nonetheless, as TL within individuals is generally strongly correlated across tissues (Daniali et al, 2013 ; Demanelis et al, 2020 ; Gurung et al, 2020 ), it is thought that leucocyte measures also serve as a marker of TL in other tissues. Cross‐sectional epidemiological studies have demonstrated positive associations between short leucocyte TL (LTL) and multiple traits of the MetS (Monickaraj et al, 2012 ; Rehkopf et al, 2016 ; Revesz et al, 2014 ; Verhulst et al, 2016 ), as well as risk of coronary artery disease (CAD) (Haycock et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, there may be unidentified pleiotropic effects in these datasets, so future investigators should analyze more MR methods and collect more data to adjust for confounding risk factors, such as LDSC (Linkage disequilibrium score) regression [ 46 ], CAUSE (Causal Analysis Using Summary Effect Estimates) [ 47 ], and GRAPPLE (Genome-wide mR Analysis under Pervasive PLEiotropy) [ 48 ]. Third, we measured leukocyte TL; however, several studies have shown a strong correlation between the TL in different tissues and pathogenic outcomes [ 12 , 49 ], and we did not obtain full summary GWAS information of telomere which renders it difficult to explore a possible bidirectional association between telomeres and hearing loss (hearing loss may be causally associated with telomere length). In addition, many of the diagnostic criteria for hearing loss in GWAS are based on self-reported hearing status rather than audiometry, which may lead to bias.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on obese men, it was found that weight and body fat loss achieved with calorie-restricted diets resulted in gains in telomere length [ 45 ]. There was no change in telomere lengths in obese individuals who lost weight with bariatric surgery [ 46 ]. Similarly, it was observed that 12 months of diet and exercise intervention did not change telomere length in post-menopausal women [ 47 ].…”
Section: Effects Of Physical Activity On Telomere Lengthmentioning
confidence: 99%